The Role of the School in Developing Student Development Tasks - Jumadil Saputra; Agung Prabowo (International Journal of Ethno-Sciences and Education Research, 2021)
The development of student life is the responsibility of the parents who gave birth to it. If we empathize and can live the dynamics of a student's psychic life, we as adults will regret having treated a child or student incorrectly. This shows that we need to know about the world of children or students both at home and at school. So that we know how necessary parents, teachers, and anyone who is engaged in the field of education understand the stages and tasks of child or student development. In this study only focused on the role of educators and teachers for student development. The purpose of this paper discusses the school efforts to achieve student development into a better person. The method used in this research is literature studies with a focus on student development. The results show the role of the school is very important for the development of students to face the world of work in the future. The explanation presented in this paper, still seems to be dominated by the opinions or findings of experts from the West. Therefore, for further research, it is necessary to conduct a more comprehensive study, both textually and contextually.